HUBUNGAN IKLIM KOMUNIKASI DAN MOTIVASI DENGAN KINERJA PEGAWAI DI LINGKUNGAN KANTOR KEMENTERIAN AGAMA KOTA LANGSA - Nur Zubaidah (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2017)
Abstract: This research aims to determine the communication climate relationship with communicationclimate and work motivation with employee of performance. The population of this research were allemployees of religion affairs at Langsa City , who had worked at least for four years. The populationamounted to fourty people and all of them used as research samples. the scope of this research is limited bythese variables.This data research were obtained using questionnaires in the form of likert scale. The Questionnaire areorganized on the basis of variable indicators and were tested to the respondents who were the researchsample. After tested is was found that all the istrumen of variables X1 consisted of 25 question and variableX2 consisted of 25 items of questions is valid and reliable. The test data analysis requirements of variable X1,X2 and Y Show that all variab are normally distributed. Then tested with shows that regression betweenvariables X1 and X2 with Y and is linear with the value p<0.05